Promotion Human Rights in Latin America: A Case Study of Brazil and Argentina - Thi Thuy Hang, Chu (VNU Journal of Science: Policy and Management Studies; Vol 38 No 2DO - 10.25073/2588-1116/vnupam.4387, 2022)
Latin America has a relatively strong legal framework and institutions for the promotion and protection of human rights at the regional and national levels. The ratification rate of international treaties on human rights is relatively high in Latin America, but it is one of the most unequal regions in the world. The article studies law and mechanisms for protection and promotion human rights in Latin America through two representative countries: Brazil and Argentina.